Analysis of the Use of English in the Promotion of Environmentally Friendly Products: Green Marketing Practices and Consumer Perceptions in Semarang - Hadi, Syamsul; Shella Gherina Saptiany; Sandy Satrio Bagaskara; Keylla Nursita Dwi Ayunda (Jurnal Maksipreneur, 2025)
This investigation examines consumer perceptions and green marketing practices in Semarang, with a particular emphasis on the use of English in promoting environmentally responsible products. Interviews with company representatives and focus group discussions with consumers are employed as qualitative research methods. The research indicates that companies have implemented a diverse array of green marketing practices; however, there are still deficiencies in their consistent and effective implementation. Green marketing practices are generally well-received by consumers, who are influenced by factors such as environmental awareness, prices, product quality, and confidence in companies' environmentally friendly claims. Diverse perceptions are generated by the utilization of English in promotional materials, with some individuals expressing apprehensions regarding potential confusion, while others find it effective in improving the product's image. The study enhances comprehension of ecological marketing strategies, and the necessity of more balanced approaches and integrated strategies in marketing communication is underscored, as well as consumer perceptions in Indonesia. Theoretical implications encompass the necessity of incorporating contextual factors into global marketing theory and the endorsement of the theory of planned behavior.  The research's limitations include the necessity for further exploration and the limited generalization, as well as recommendations for future research.